Pathological CTG leading to emergency caesarean section and its perinatal outcome in Hospital Raja Perempuan Zainab II, Kota Bharu - Rabindran, Gandhi (2008)
To evaluate the perinatal outcomes of infants who had pathological CTGs resulting in emergency caesarean section as a mode of delivery. A cross sectional study was conducted from the 1st of June 2006 to 31st of May 2007 in Hospital Raja Perempuan Zainab II , Kota Bharu. One hundred and forty five patients who had pathological CTGs in labour had emergency caesarean sections. The neonates were assessed in terms of their Apgar scores at 1 and 5 minutes of life and had their umbilical artery pH recorded. The type of anaesthesia used, duration between decision of caesarean section and delivery of neonates, appearance of liquor and the variability of the CTGs were also recorded. In this study only 25 (17.25%) out of 145 neonates had an umbilical artery pH ofless than 7.2. Out ofthe 145 neonates, only 21 (14.49%) had an Apgar score of below 7 at 1 minute and only 1 (0.7%) neonate had an Apgar score of below 7 at 5 minutes of life. The mean umbilical artery pH was 7.26. Spinal anaesthesia was 3.4 times more commonly used than general anaesthesia. The mean duration between decision of caesarean section and delivery was 59.9 minutes. The most common variability seen was in the group of more than 25 which was 68 (46.9%), the commonest liquor observed was clear in nature which was 71 (49%) in number, the commonest baseline heart rate of 110-160 was seen in 116 (80%), the commonest deceleration was late deceleration which was seen in 62 (42.8%) CTGs and acceleration was absent in 129 (89%) CTGs. There was no association between the time taken between decision and delivery of neonates with umbilical artery pH and Apgar scores at 1 and 5 minutes. There was an association between the different groups of baseline heart rate, different types of decelerations, different types of liquor and variabilities of the CTGs with umbilical artery pH and Apgar scores at 1 and 5 minutes. There is also an association between the presence and absence of acceleration with umbilical artery pH and Apgar score at 1 minute, but there was no association with Apgar score at 5 minutes. CTG alone is a poor predictor of fetal hypoxia in labour resulting in an increase in caesarean sections.